2002
DOI: 10.1093/milmed/167.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Coxa Saltans Externa Treated with Z-Plasty of the Iliotibial Tract in a Military Population

Abstract: Coxa saltans, or snapping hip, can be attributable to a number of causes. Coxa saltans externa typically occurs when the thickened portion of the iliotibial band snaps over the greater trochanter as the hip is flexed. This condition generally resolves with a course of nonoperative treatment. We have treated three patients with Z-plasty of the iliotibial band, which has the highest published success rate in the English language literature. Only one of three patients was able to return to full activities postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The prevalence of the snapping hip syndrome in general population is not clear, but most of the patients across different studies were either young females (7,8) or military recruits (7,9). Winston et al (8) reported snapping hip to be as high as 90 percent in ballet dancers, with 80 percent of them had bilateral symptoms.…”
Section: Sharda Et Al mentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of the snapping hip syndrome in general population is not clear, but most of the patients across different studies were either young females (7,8) or military recruits (7,9). Winston et al (8) reported snapping hip to be as high as 90 percent in ballet dancers, with 80 percent of them had bilateral symptoms.…”
Section: Sharda Et Al mentioning
confidence: 99%
“…However, most studies agree that the symptoms are rarely severe enough to warrant surgical intervention (8)(9)(10)(11), which should only be performed as a last resort. Most patients improve with a trial of conservative treatment typically includes stretching exercises.…”
Section: Sharda Et Al mentioning
confidence: 99%
See 2 more Smart Citations
“…Nonoperative management, including physical therapy and anti-inflammatory medications, is often adequate to relieve symptoms; however, refractory cases may require surgical intervention [22]. Surgical treatment of these conditions has historically required open procedures to lengthen either the iliopsoas tendon or iliotibial band [10,14,22,30] or to remove the offending intra-articular pathology [22]. Current arthroscopic techniques allow for both trans-articular iliopsoas and extra-articular iliotibial band releases.…”
Section: Arthroscopic Management Of Chondral Lesionsmentioning
confidence: 99%